Space and Place in the Contemporary Italian Crime Fiction: The Case of Imma Tataranni and Lolita Lobosco - Marić, Antonela (Anafora, 2025)
The aim of this paper is to examine the role of space in contemporary Italian crime fiction, focusing in particular on works by Gabriella Genisi and Mariolina Venezia, and their two protagonists, deputy prosecutor Imma Tataranni and deputy chief Lolita Lobosco. The paper argues that space and its features are pivotal to the narrative. Space goes beyond serving as a mere backdrop; it actively mirrors and shapes social and cultural dynamics within crime fiction (Gabellieri). Drawing on theorists such as Gaston Bachelard, this study highlights how spaces infused with human values can evoke “topophilia,” a profound sense of belonging, which in turn supports cultural identity and connection to a place. The selected novels show a strong belonging to place and show how serious social issues, such as corruption, land speculations, the ecomafia, profit, and the like, can influence engagement with space. The cities of Bari and Matera, each with their distinct characters, illustrate this impact: Matera is regarded for its historical and cultural richness, while Bari reveals a complex modernity. Yet, both cities are marred by crime and social challenges. This duality is explored as both picturesque and unsettling, influencing the identity of the region. This paper demonstrates how these spaces engage readers emotionally, becoming central to plot and character development. By integrating geographical and cultural elements, we underscore how spatial settings are as vital as characters in shaping the depth and resonance of Italian crime fiction.